2004
DOI: 10.1124/jpet.104.066399
|View full text |Cite
|
Sign up to set email alerts
|

Submandibular Gland Acinar Cells Express Multiple α1-Adrenoceptor Subtypes

Abstract: We evaluated an acinar cell line (SMG-C10) cloned from rat submandibular glands as a possible model for ␣ 1 -adrenoceptor regulation of submandibular function. ␣ 1 -Adrenoceptors are subdivided into three subtypes called ␣ 1A , ␣ 1B , and ␣ 1D , which can be distinguished from one another by their differential affinity values for subtype-selective ␣ 1 -adrenoceptor antagonists. Thus, ␣ 1 -adrenoceptor subtypes in SMG-C10 cells were characterized with reverse transcription-polymerase chain reaction (RT-PCR) and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 18 publications
(20 reference statements)
1
16
0
Order By: Relevance
“…For example, in a recent study, mRNA for all three ␣ 1 -AR subtypes was detectable in rat submandibular gland cells. However, BMY 7378 detected only a single population of low-affinity binding sites in radioligand binding experiments (Bockman et al, 2004), which is consistent with our findings suggesting that coexpression of ␣ 1B -and ␣ 1D -ARs results in the masking of high-affinity ␣ 1D -AR binding sites. In addition, the affinity of BMY 7378 in inhibiting phenylephrine-mediated contraction was found to be significantly increased in isolated carotid arteries from ␣ 1B -AR knockout mice (Deighan et al, 2005), and phenylephrinestimulated increases in left ventricular-developed pressure were only inhibited by BMY 7378 in ␣ 1A -/␣ 1B -AR double knockout mice (Turnbull et al, 2003).…”
Section: Discussionsupporting
confidence: 81%
“…For example, in a recent study, mRNA for all three ␣ 1 -AR subtypes was detectable in rat submandibular gland cells. However, BMY 7378 detected only a single population of low-affinity binding sites in radioligand binding experiments (Bockman et al, 2004), which is consistent with our findings suggesting that coexpression of ␣ 1B -and ␣ 1D -ARs results in the masking of high-affinity ␣ 1D -AR binding sites. In addition, the affinity of BMY 7378 in inhibiting phenylephrine-mediated contraction was found to be significantly increased in isolated carotid arteries from ␣ 1B -AR knockout mice (Deighan et al, 2005), and phenylephrinestimulated increases in left ventricular-developed pressure were only inhibited by BMY 7378 in ␣ 1A -/␣ 1B -AR double knockout mice (Turnbull et al, 2003).…”
Section: Discussionsupporting
confidence: 81%
“…Similarly, an α 1D -adrenoceptor-selective concentration of BMY 7378 (10 nM) had little effect on phenylephrinestimulated ERK1/2 activation (8% inhibition). In contrast, 30 μM chloroethylclonidine for 12 min, a treatment that we previously showed to inactivate only the α 1B -adrenoceptor subtype in SMG-C10 cells (Bockman et al, 2004), significantly inhibited (p < 0.05 ) phenylephrinestimulated ERK1/2 activation (Fig. 4A).…”
Section: Functional Characterization Of the α 1 -Adrenoceptor Subtypementioning
confidence: 73%
“…Where it was appropriate, cells or gland slices were incubated with a competitive receptor antagonist or an inhibitor for 30 min before agonist addition. In some experiments, cells were pretreated with the irreversible α 1B -adrenoceptor antagonist, chloroethylclonidine, as previously described (Bockman et al, 2004). Briefly, cells were incubated with 30 μM chloroethylclonidine for 12 min at 37 °C.…”
Section: Erk1/2 Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the ␣ 1D -AR is indeed expressed in the vasculature and contributes to maintenance of blood pressure-a contention that is also evident from the reduced blood pressure and impaired vasoconstrictor responses to norepeinephrine of ␣ 1D -knockout mice (Tanoue et al, 2002)-but that its expression is masked by the coincident expression of the ␣ 1B -AR. Of course, this interpretation, and the increasingly robust evidence suggesting that endogenously expressed ␣ 1 -ARs heterodimerize, is predicated on more than one ␣ 1 -AR subtype being expressed in a single cell, a contention supported by studies of various cell lines (Esbenshade et al, 1993;Bockman et al, 2004), albeit one that has not yet been definitively demonstrated using a single isolated cell.…”
mentioning
confidence: 91%